Heart block following topical latanoprost treatment. (7th October 2011) - De Smit, Elisabeth; Theodorou, Maria; Hildebrand, Göran Darius; Bloom, Philip
Abstract : The authors report a case of second degree heart block associated with topical latanoprost treatment. The authors discuss the possibility of a causative effect as the cessation of this treatment resulted in improvement of the arrhythmia. The authors highlight previous reports and research in humans and animals which demonstrate an association of arrhythmias with prostaglandin analogues. This report draws attention to the possibility that an extremely commonly prescribed topical drug may trigger arrhythmias in susceptible individuals. It is important that prescribers are aware of this possible side-effect.